Calculation of One- particle redial distribution function and One- particle expectation value for K(1S) shell of He and Li atoms by Using Correlated function - حسن, علياء عبد المحسن (University of Thi-Qar Journal of Science, 2014)
The electronic correlation effect is the most important effectiveness in physics, which make changed in many physical result specially with that of atomic activeness. The approximation ,which study the electronic correlation is called "correlated function" .Sample of the correlated has been used in this study ,that function is the J.D. Stuart- F.A .Matson function by make change on the original formula .That function is of configuration interaction of virtual orbitals. That was for two electrons for study some of atomic propertes the one particle radial distribution function  D(r 1 ) and one particle expectation value n= r 1   for K(1 S ) shell of He and Li atoms .The results wear successful for giving the results that refer to an acceptable correlated function.